Strain Differences in Responsiveness to Repeated Restraint Stress Affect Remote Contextual Fear Memory and Blood Transcriptomics. (15th September 2020) - Jung, Seung H.; Meckes, Jeanie K.; Schipma, Matthew J.; Lim, Patrick H.; Jenz, Sophia T.; Przybyl, Katherine; Wert, Stephanie L.; Kim, Sarah; Luo, Wendy; Gacek, Stephanie A.; Jankord, Ryan; Hatcher-Solis, Candice; et al.
Highlights: Fear memory is strain dependent; greater in the less stress-reactive strain. Repeated stress attenuates remote fear memory, but only in the less stress-reactive strain. Strain neutral, stress-responsive genes are putative blood-based stress biomarkers. Strain-specific stress-responsive genes are putative blood markers of vulnerability to stress. Abstract: The role of stress in altering fear memory is not well understood. Since individual variations in stress reactivity exist, and stress alters fear memory, exposing individuals with differing stress-reactivity to repeated stress would affect their fear memory to various degrees. We explored this question using the average stress-reactive Fisher 344 (F344) rat strain and the Wistar–Kyoto (WKY) strain with its heightened stress-reactivity. Male F344 and WKY rats were exposed to the contextual fear conditioning (CFC) paradigm and then chronic restraint stress (CRS) or no stress (NS) was administered for two weeks before a second CFC. Both recent and reinstated fear memory were greater in F344s than WKYs, regardless of the stress status. In contrast, remote memory was attenuated only in F344s after CRS. In determining whether this strain-specific response to CRS was mirrored by transcriptomic changes in the blood, RNA sequencing was carried out. Overlapping differentially expressed genes (DEGs) between NS and CRS in the blood of F344 and WKY suggest a convergence of stress-related molecular mechanisms, independent of stress-reactivity. In contrast, DEGs unique to the F344 and the WKY stress responses are divergent in their functionality and networks, beyond that of strain differences in their non-stressed state. These results suggest that in some individuals chronic or repeated stress, different from the original fear memory-provoking stress, can attenuate prior fear memory. Furthermore, the novel blood DEGs can report on the general state of stress of the individual, or can be associated with individual variation in stress-responsiveness.